2021
DOI: 10.1088/1361-6560/abee58
|View full text |Cite
|
Sign up to set email alerts
|

Solving the volumetric modulated arc therapy (VMAT) problem using a sequential convex programming method

Abstract: The volumetric modulated arc therapy (VMAT) problem is highly non-convex and much more difficult than the fixed-field intensity modulated radiotherapy optimization problem. To solve it efficiently, we propose a sequential convex programming algorithm that solves a sequence of convex optimization problems. Beginning by optimizing the aperture weights of many (72) evenly distributed beams using the beam’s eye view of the target from each direction as the initial aperture shape, the search space is constrained to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Expanding this work to VMAT has been technically very challenging due mainly to the non-convexity and the growing size of the resultant optimization problems. In this work, we proposed an automated VMAT algorithm based on SCP (Dursun et al 2021) and constrained hierarchical optimization. We proposed novel convex surrogate metrics for incorporating plan complexity and promoting aperture regularity and neighboring aperture similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding this work to VMAT has been technically very challenging due mainly to the non-convexity and the growing size of the resultant optimization problems. In this work, we proposed an automated VMAT algorithm based on SCP (Dursun et al 2021) and constrained hierarchical optimization. We proposed novel convex surrogate metrics for incorporating plan complexity and promoting aperture regularity and neighboring aperture similarity.…”
Section: Discussionmentioning
confidence: 99%
“…The dose constraint and optimization parameters of the three plans were the same ones, and the dose calculation grid size was 2.5 mm, using the AAA dose algorithm. [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…Palma et al reported that the most favorable equivalent uniform doses and lowest doses to organs at risk were achieved with variable dose-rate VMAT, which was statistically significantly better than 5-field, IMRT for rectal and femoral head endpoints and better than constant dose-rate VMAT for most bladder and rectal endpoints. [11][12][13] Multiple groups have observed that VMAT reduces beam-on time and the radiation dose relative to 7 to 9 field IMRT.…”
Section: This Study Was Supported By the Zhongshan Science And Techno...mentioning
confidence: 99%
“…In this work, we employ our in-house automated treatment planning system, internally referred to expedited constrained hierarchical optimization (ECHO), to generate consistent high-quality plans as an input for our DL model. ECHO generates consistent high-quality plans by solving a sequence of constrained large-scale optimization problem [28,29,30,31,32,33]. ECHO is integrated with Eclipse and is used in our daily clinical routine, with more than 4000 patients treated to date.…”
Section: Introductionmentioning
confidence: 99%